Social Consequences and Contexts of Adverse Childhood Experiences - Trinidad, Jose Eos R (Archīum Ateneo, 2021)
Adverse childhood experiences' (ACEs) negative consequences on health, education, and life opportunities are often explained through the neurodevelopmental changes in a person's stress reactivity and coping, which contribute to the adoption of health-damaging and antisocial behaviors. However, such focus on the biological dimension eclipses the equally important social dimension of adversity, in particular, how adversities at home can influence association with peers who exhibit and can exacerbate negative behaviors like early and binge drinking, illegal drug use, and gang involvement. More than the consequences for peer formation, this study also investigates the contexts in which ACEs are most predictive. Using a longitudinal study of US youths who were adolescents in 2007 and young adults in 2017, I find that experiencing adversity predicted involvement in peers exhibiting negative behaviors. However, the consequences of ACEs are not similar for everyone and for every outcome: (1) In disadvantaged families where ACEs were most likely, experiencing adversity influenced having peers in gangs but not the other outcomes. (2) In the most advantaged families where ACEs were least likely, having an ACE only predicted adult peers' regular drug use. (3) In families who were in the middle, experiencing adversity predicted early and binge drinking among peers. Taken together, they suggest that complex social processes and environments operate in the negative effects of ACEs, and the present research suggests a method to investigate how ACEs' impact may differ according to one's social context.